Readdressing Dhaka’s Public Water Bodies: a Design Research - Peeters, Sanne; Shannon, Kelly (Nakhara : Journal of Environmental Design and Planning, 2011)
In Dhaka, the capital of Bangladesh, rampant expansion and commercial development are brutally transforming the urban tissue. As a consequence, Dhaka’s water network, which was once integrated into the city’s fabric and is of major importance for its drainage capacity, is rapidly disappearing. This article critically investigates the layered meanings of water in the city through focusing on the case study of Hatirjheel Lake, Dhaka’s largest inner-city water body. A number of interpretative maps dissect the rich history of the city and its water, while contemporary cartographies reveal a new set of issues as advancing urbanization fi lls in water bodies. Beyond mere descriptive urbanism, the paper is also projective and proposes design as research by way of a conclusion. The tools of urban and architectural design are utilized for a project on Hatirjheel Lake that could restore and enlarge land/water and culture/nature relationships.